Canalicular adenoma of the minor salivary gland in the upper lip: case report - Stramandinoli-Zanicotti, Roberta Targa; Cesa, Thiago Serafim; Giustina, Jean Della; Bahr, Joao Augusto; Schussel, Juliana Lucena; Sassi, Laurindo Moacir (Journal of Oral Diagnosis, 2016)
Canalicular adenoma is a rare benign tumor of the minor salivary glands that is the most prevalent in older adults (mean age, 60 years). The upper lip is the most commonly affected site, followed by the buccal mucosa and palate. It presents as a nodular lesion without a tendency for recurrence. Here, we describe a case of canalicular adenoma presenting as a nodular, painful mass in the upper lip of a 62-year-old man with a history of trauma. Fine needle aspiration biopsy yielded inconclusive results but excluded malignancy. The lesion was enucleated, and a definitive diagnosis of canalicular adenoma was established by histological and immunohistochemical analyses. No signs of recurrence were noted at the 8-month follow-up examination. The case emphasizes the importance of differential diagnosis of nodular lesions in the oral mucosa for appropriate treatment and histological analysis for definitive diagnosis.